Charakteristika nákladů pojišťovny v kontextu mezinárodního porovnání s legislativou - Meluchová, Jitka (Univerzita Pardubice, 1999)
The monitoring of the particular cost components in an insurance company according to the purpose of their expenditure requires experience for creating an information system which identifies the arrised costs and considers their direction. Especially by the indirect insurance costs it is sometimes difficult to determine for what purpose they were expended, if acquisition or overhead costs are concerned. This requises to analyse the particular cost components depending on the organizational division of the insurance company and on the bases of this analyses to allocate the costs according to chosen allocation bases or a qualified estimation.
Keywords: Pojišťovny; Náklady; legislativa; Evropská Unie; porovnání